Shotgun proteomics reveals changes in the pectoralis major muscle of broilers supplemented with passion fruit seed oil under cyclic heat stress conditions - Sávio de Almeida Assunção, Andrey [UNESP]; Aparecida Martins, Renata [UNESP]; Cavalcante Souza Vieira, José [UNESP]; Campos Rocha, Leone [UNESP]; Kaiser de Lima Krenchinski, Fernanda [UNESP]; Afonso Rabelo Buzalaf, Marília; Roberto Sartori, José [UNESP]; de Magalhães Padilha, Pedro [UNESP] (Elsevier, 2023)
The aim of this study was to characterize the proteins differentially expressed in the pectoralis major muscle of broilers supplemented with passion fruit seed oil (PFSO) under cyclic heat stress conditions. Ninety one-day-old male chicks were housed in cages arranged in a climatic chamber, where they were kept under cyclic heat stress for eight hours a day from the beginning to the end of the experiment. The birds were divided into two experimental groups, one group supplemented with 0.9% PFSO and a control group (CON) without PFSO supplementation. At 36 days of age, 18 birds were slaughtered to collect muscle samples. From pools of breast fillet samples from each group, proteolytic cleavage of the protein extracts was performed, and later, the peptides were analyzed by liquid chromatography-tandem mass spectrometry (LC-MS/MS). The 0.9% PFSO supplementation revealed the modulation of 57 proteins in the pectoralis major muscle of broilers exposed to cyclic heat stress. Among them, four proteins were upregulated, and 46 proteins were downregulated. In addition, seven proteins were expressed only in the CON group. These results suggest that PFSO may increase heat tolerance, with a possible reduction in oxidative stress, activation of neuroprotective mechanisms, protection against apoptosis, decrease in inflammatory responses, and regulation of energy metabolism.
Keywords: Gel-free; LC-MS/MS; Oxidative stress